(untitled) (European Journal of Formal Sciences and Engineering, 2023)
In the present paper, we analyzed the main advantages of the active confinement techniques with a particular focus on the CAM system, which is an Italian reinforcement technique with pre-tensioned stainless steel ribbons. Italian seismic codes classify the CAM system as belonging to the strengthening category of “horizontal and vertical ties”. Therefore, we compared the CAM system to the reinforcement techniques with horizontal and vertical ties in order to understand the actual similarities and possible differences between them. Moreover, we offered a deep analysis of the main critical issues of the CAM system, distinguishing between geometrical and mechanical weak-points. In particular, we analyzed the strengthening mechanism of the CAM system, still poorly understood, by performing a static analysis in the Mohr/Coulomb plane. Finally, we provided suggestions for future developments.